Produksi Serasah Empat Jenis Tumbuhan Mangrove Di Desa Lalombi Kabupaten Donggala - Susanti Susanti; Samsurizal M. Suleman; Ramadhanil Ramadhanil (Biocelebes, 2013)
Research on Litter production of four types of mangrove plant in Lalombi Village, Donggala was carried out from December 2012 to February 2013. Mangrove populations that become the object of observation in this study were Sonneratia alba J. Smith, Bruguiera gymnorrhiza (L.) Lamk., Rhizophora apiculata BL., dan Rhizophora mucronata Lamk. This study was done based on Survey method, and the litter sample was collected by using net reservoir. The collection of litter was done every 2 weeks, and then separated according to the type of litter and its components such as leaves, twigs and reproduction organs and then dried at a temperature of 103 °C until constant weight. The resultss showed that the total production of four types of mangrove plant litter was 3.44 tons/ha/3 months. The contribution component of the leaves were 2.23 tons/ha/3 months, twigs were 0.53 tons/ha/3 months and reproduction organs were 0.68 tons/ha/3 months. Among the mangrove plant species observed, Sonneratia alba was produce the highest litter than others. Litter production of Sonneratia alba, Rhizophora mucronata, Rhizophora apiculata and Bruguiera gymnorrhiza, were 1.28 tons/ha/3 months, 1.09 tons/ha/3 months, 0.64 tons/ha/3 months and 0.44 tons/ha/3 months respectively. Key words: Litter production, Mangrove, Lalombi village.